Prevalence and Risk Factors of Anemia among Children 6–59 Months Old in Haiti - Mohamed Ag Ayoya; Ismael Ngnie-Teta; Marie Nancy Séraphin; Aissa Mamadoultaibou; Ellen Boldon; Jean Ernst Saint-Fleur; Leslie Koo; Samuel Bernard (Anemia)
Anemia has serious consequences on child growth, development, and survival. This study was conducted in Fond des Blancs and Villa, Haiti, to assess the prevalence of childhood anemia and its risk factors in order to inform program design. Children 6–59 months old (n=557) were selected using a cross-sectional multistage sampling methodology. Hemoglobin was measured using the HemoCue technique. Descriptive and multivariate analyses were performed to determine prevalence and factors associated with anemia. The prevalence of childhood anemia was 38.8% (23.9% mild, 14.7% moderate, and 0.2% severe). Mean hemoglobin was 11.2±1.2 g/dL. Variables associated with child anemia were age less than 24 months (OR=2.6; P=0.000), stunting (OR=2.2; P=0.005), and mother’s low hemoglobin level (OR=1.8; P=0.011). Anemia among young children in Fond des Blancs and Villa is a public health problem. Predictors of child anemia in this region include child’s age, stunting, and mother’s anemia. Interventions and strategies aimed at addressing effectively anemia in this population must therefore target mothers and children under two years of age.